2018
DOI: 10.20517/2394-4722.2017.60
|View full text |Cite
|
Sign up to set email alerts
|

Targeting adenosine receptor 2B in triple negative breast cancer

Abstract: In the review "Role of adenosine in tumor progression: focus on A2B receptor as potential therapeutic target", Sorrentino and Morello make a compelling case for considering adenosine 2B receptor (A2BR) as a target in cancer therapy (J Cancer Metastasis Treat 2017;3:127-38). A large body of evidence has accumulated suggesting A2BR to play an active role in tumor immune suppression and metastasis. Thus, this commentary will discuss the intriguing possibility of targeting A2BR in specific breast cancers that expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, signals related to this pathway have been associated with drug resistance (or poor clinical outcomes) in breast cancer. For example, CD163-mediated anti-inflammatory response 22,23 , Adenosine receptor 2B (ADORA2B) mediated anti-inflammatory cytokines production 24 and IL10 synthesis that plays a role in immune escape 25 . Together, our finding supports the current knowledge that cellular activity in the mTOR signaling pathway might affect the drug sensitivity in tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, signals related to this pathway have been associated with drug resistance (or poor clinical outcomes) in breast cancer. For example, CD163-mediated anti-inflammatory response 22,23 , Adenosine receptor 2B (ADORA2B) mediated anti-inflammatory cytokines production 24 and IL10 synthesis that plays a role in immune escape 25 . Together, our finding supports the current knowledge that cellular activity in the mTOR signaling pathway might affect the drug sensitivity in tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it was also revealed that Ado stimulated the expression of VEGF, which leads to enhanced intratumoral blood flow and angiogenesis by mediating purinergic P1 receptors, i.e., A2BR. Likewise, apart from VEGF, the activation of A2BR within the microvasculature also regulates the expression of other angiogenic factors like IL-8 and bFGF as well as results in the proliferation of cells which have an impact on cancer growth, invasion, and migration by inducing neo-vascularization within surrounding areas of cancer [36,37].…”
Section: Adenosine 2b Receptor (A2br)mentioning
confidence: 99%
“…Mittal et al [7] suggested that high A 2B AR expression is associated with worse prognoses in triple-negative breast cancer (TNBC). In a TNBC mouse model, A 2B AR activation increased metastasis [42], while A 2B AR antagonism in mouse models reduced the tumor burden by immune mechanisms and action on tumor cells. The high A 2B AR expression has also been found in many human tumor cell lines, such as PC3 prostate, T24 bladder, 1321N1 astrocytoma [35], U373MG astrocytoma [43], MDA-MB-231 breast [20], Jurkat T cells [44], BON-1 pancreatic and KRJ-I intestinal [45], A375 melanoma [46], and THP-1 human monocytes [47].…”
Section: A2bar Distribution and Expressionmentioning
confidence: 99%